2017
DOI: 10.1002/andp.201700031
|View full text |Cite
|
Sign up to set email alerts
|

Sub‐Monolayer Growth of Titanium, Cobalt, and Palladium on Epitaxial Graphene

Abstract: We deposited metals (Ti, Co, Pd) typically used as seed layers for contacts on epitaxial graphene on SiC(0001) and studied the early stages of growth in the sub-monolayer regime by Scanning Tunneling Microscopy (STM). All three metals do not wet the substrate and Ostwalt ripening occurs at temperatures below 400 K. The analysis of the epitaxial orientation of the metal adislands revealed their specific alignment to the graphene lattice. It is found that the apparent height of the islands as measured by STM str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 40 publications
2
6
0
Order By: Relevance
“…They neither discriminate the surface configurations between H-Gr (hydrogenated Gr) and (6 × 6) Gr (Gr on buffer layer) domains. In spite of this, we note that AFM is very often used to show the homogeneity of Gr thin films, in particular, to be processed in various devices or before deposition of further epitaxial layers, for example, for the growth of van der Waals heterostructures, whereas the Gr atomic structure has a strong influence on both the electronic properties of Gr and on the adsorption energy of many species and their subsequent growth mode …”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…They neither discriminate the surface configurations between H-Gr (hydrogenated Gr) and (6 × 6) Gr (Gr on buffer layer) domains. In spite of this, we note that AFM is very often used to show the homogeneity of Gr thin films, in particular, to be processed in various devices or before deposition of further epitaxial layers, for example, for the growth of van der Waals heterostructures, whereas the Gr atomic structure has a strong influence on both the electronic properties of Gr and on the adsorption energy of many species and their subsequent growth mode …”
Section: Resultsmentioning
confidence: 94%
“…In spite of this, we note that AFM is very often used to show the homogeneity of Gr thin films, in particular, to be processed in various devices or before deposition of further epitaxial layers, for example, for the growth of van der Waals heterostructures, whereas the Gr atomic structure has a strong influence on both the electronic properties of Gr and on the adsorption energy of many species and their subsequent growth mode. 67 The developed CVD process, which involves a combination of complex processes based on the interaction of H 2 /Ar and C 3 H 8 , is very robust and reliable. We have shown that it produces a uniform ML Gr on a full-sample scale, whose atomic properties [H-Gr or (6 × 6) Gr] can be varied at will, by tuning the H 2 /Ar flow rate.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…We predict the thermodynamic and kinetic relationships and measurement strategies described here may be applicable to metals that have been previously found to exhibit epitaxy on bulk or supported vdW materials: Cu, Ag, Pd, Co, Rh, Eu, Gd, Dy, and Pb, among others. , , Ab initio calculations also predict that most of the 3d and group 10 transition metals, noble metals, and rare earth metals should exhibit a 3D growth mode on Gr, a result our studies suggest could be more broadly applied to other 2D materials. This opens boundless combinations of metals and 2D materials available for faceted 2D/3D heterointegration.…”
mentioning
confidence: 85%
“…The relatively weak quasi-vdW bonding enables sharp interfaces and avoids the requirements of lattice matching in conventional epitaxy . Quasi-vdW epitaxy is well-known for faceted nanoislands of Au, Ag, and Au–Pd alloys on graphite; Ag, Au, and Cu on molybdenite (bulk MoS 2 ); and Au on bulk WTe 2 , WS 2 , and WSe 2 crystals. , Scanning tunneling microscopy (STM) studies have probed quasi-vdW epitaxy for numerous metals (Au, Ti, Co, Pd, Pt, Rh, Ir, W, Re, Eu, Gd, Dy, Fe, and Pb) on thin but supported 2D materials, such as monolayer graphene on SiC, Ru(0001), and Ir(111), where the substrate underneath the graphene was found to play a defining role in the metal morphology. ,, …”
mentioning
confidence: 99%
“…Detailed analysis (see below) shows that the aspect ratio actually decreases slowly with particle size (or the average particle thickness stays more constant with coverage than in the ideal case where the aspect ratio is truly constant). The flat-topped shape of Pd particles was also seen in STM on the HOPG surface 28 at room temperature and also at higher temperatures (400 K on graphene 25 and 700 K on HOPG 22 ). When Ni is deposited on this same graphene(0001)/Ni(111) surface at room temperature, it also grows rather flat-topped islands with small aspect ratios and a fixed number per unit area.…”
Section: T H Imentioning
confidence: 65%